2014
DOI: 10.21608/jfds.2014.53227
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Biological and Sensory Evaluation of Biscuit Enriched With, Iraqi Dates, Sweet Lupine and Defatted Soybean Flour.

Abstract: The objective of this study aimed to increase the nutritional and biological value of low cost biscuits to fight malnutrition among infants and young children. To produce biscuits, two of legumes flour (defatted soybean flour, whole meal flour of sweet lupine) and date (at tamr stage), were utilized in replacing part of wheat flour at three levels (5,10 and 15%). The products were analyzed for chemical, organoleptic and biological properties. The results indicated that legume flours were extremely rich in mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…The essential and non-essential amino acids content of raw materials used in different formula preparation were shown in Table (3). The total number of essential amino acids for skim milk powder being (42.74g/100 protein) it was the highest one compare in others, that agreement with Ibrahim et al,(2014). The data also in the same Table indicate that Glutamic (GLU) amio acid content had highest level in all raw materials that used in this study compare with other determined amino acids, while Tryptophan (TRY) had lowest level.…”
Section: Amino Acids Content Of Raw Materials Used In Complementary Isupporting
confidence: 81%
See 1 more Smart Citation
“…The essential and non-essential amino acids content of raw materials used in different formula preparation were shown in Table (3). The total number of essential amino acids for skim milk powder being (42.74g/100 protein) it was the highest one compare in others, that agreement with Ibrahim et al,(2014). The data also in the same Table indicate that Glutamic (GLU) amio acid content had highest level in all raw materials that used in this study compare with other determined amino acids, while Tryptophan (TRY) had lowest level.…”
Section: Amino Acids Content Of Raw Materials Used In Complementary Isupporting
confidence: 81%
“…Total number of essential amino acids ranged from (25.36 to 34.53 g/100g protein) of formula F3 and F5 respectively which contained. The total amino acids content of F5 is higher than other formulas, control and (RDA) as shown in table (7) is likely to be due to the high percentage of partially defatted soybeans flour as mentioned by Ibrahim et al, (2014). In addition of that used raw materials have different levels of amino acids as showed in Table (3) which Contributed in an increase and balance of amino acid in formulas as mention as reported by (Udensi et al, 2012).…”
Section: Amino Acids Content Of Complementary Infant Foodmentioning
confidence: 77%
“…The substitution partially of yellow corn flour with sweet lupine powder caused gradual increases in all investigated minerals contents of gluten-free biscuits samples with increasing the amount of replacement (blend 1, 2 and 3), the increment in minerals contents of studied biscuits probably regard to the relatively large amount of minerals in sweet lupine powder compared with yellow corn flour, as appeared in Table (2). Analogical investigations were obtained by Ibrahim et al (2014) who found an increase in all elements content of biscuits after replacing portions of wheat flour with sweet lupine powder (5, 10 and 15%).…”
Section: Effect Of Composite Flour On Gluten-free Biscuits Characteri...supporting
confidence: 71%